Irving Thalberg : Boy Wonder to Producer Prince. - Vieira, Mark A. (University of California Press, 2009)
Hollywood in the 1920s sparkled with talent, confidence, and opportunity. Enter Irving Thalberg of Brooklyn, who survived childhood illness to run Universal Pictures at twenty; co-found Metro-Goldwyn-Mayer at twenty-four; and make stars of Lon Chaney, Norma Shearer, Greta Garbo, Joan Crawford, Clark Gable, and Jean Harlow. Known as Hollywood's "Boy Wonder," Thalberg created classics such as Ben-Hur, Tarzan the Ape Man, Grand Hotel, Freaks, Mutiny on the Bounty, and The Good Earth, but died tragically at thirty-seven. His place in the pantheon should have been assured, yet his films were not re.